Anti-Ricket Deficiency Status among Indian Adolescents - Iyer, Sandhya; Sengupta, Caesar; Velumani, A. (Asian Journal of Biological and Life Sciences, 2015)
Vitamin D or the sunshine vitamin is a very critical nutrient and the best mode to obtain this vital factor is through direct exposure to the UVB rays of sunlight. However, deficiency of this easily obtainable nutriment is very high in our country. Inspite of being tropical, which receives sunlight all through the year, many factors have fueled vitamin D deficiency among all strata of the society. Data of a total of 517 adolescents were included for analysis. Serum 25-OH vitamin D levels were tested using liquid chromatography - mass spectrometry platform and reported. Along with the total serum vitamin D levels, individual levels of vitamin D2 as well as vitamin D3 was also recorded for analysis. Our report highlights total prevalence of vitamin D deficiency to be as high as 61%, with it being higher among adolescent girls at 63% compared to boys at 56%, though the difference is not statistically significant. Also, average levels of 25-OH vitamin D has been detected to be 13.04 ng/mL among the deficient subjects, while levels of vitamin D2 and D3 have been detected to be at 1.64 ng/mL and 11.43 ng/mL respectively. The finding highlights prevalence of high frequency of deficients among adolescents. This enforces the need to generate massive awareness among Indians, as deficiency of this vitamin in young age, becomes a pedestal for development of many more clinical ailments.
Keywords: Adolescents; Anti-ricket; Deficiency; Indian; Vitamin D